(untitled) (Albayan Scientific Journal, 2023)
Ten random samples were collected from two sites in the city of Tobruk for the purpose of the study, the first site was from Al-Haj Ahmed Atallah grape farm at the east entrance of the city and the second site was from a Faculty of sciences belonging land and transported immediately to laboratory Botany department for analysis. inoculated on CZAPEK DOX AGAR and incubated at 25±2 C° and observed for 4-7 days after which the different colonies obtained were identified using the slide culture technique. The pathogenic fungal analysis shows that, Mucor sp has the highest frequency of occurrence (33.3 %) followed by Aspergallius spp (32.8 %) then Penicilium spp (22%) Alternaria spp with (20.8 %) Rhizoctonia solani (19.4) and Fusarium spp (14.9) frequency of occurrence.